Societal risk factors for overweight and obesity in women in Zimbabwe: a cross-sectional study - Nancy T. Mangemba; Miguel San Sebastian (BMC, 2020)
Abstract Background Overweight and obesity are well-recognized risk factors for various non-communicable diseases. Evidence shows an increasing burden of overweight and obesity in low and middle-income countries, especially in women. Little is known about the risk factors in Zimbabwe. The aim of this study was to determine the socioeconomic risk factors for overweight and obesity in non-pregnant adult Zimbabwean women. Methods A cross-sectional study was conducted using the 2015 Zimbabwe Demographic Health Survey (n = 8904) data on the adult female population aged 15 to 49. Body mass index (BMI) was calculated by dividing the body weight by height squared. The socio-economic variables studied were age, marital status, residence, province, religion, education, household wealth index, household size, access to mass media and the use of contraception. Prevalence of overweight (BMI ≥ 25-29.9 kg/m2) and obesity (BMI ≥30 kg/m2) were determined. Simple and multivariable logistic regressions were then used to ascertain any relationships. Results The weighted prevalence of overweight and obesity in adult females was 34.2 and 12.3% respectively. The odds for being overweight and obese were significantly higher with increasing age (Adjusted Odds Ratio (AOR 2.76, 95% CI:2.45-3.11 for overweight and AOR 3.24, 95% CI:2.69-3.90 for obesity) with marriage (AOR 1.58, 95% CI:1.38-1.79 for overweight and AOR 1.54, 95% CI:1.27-1.87 for obesity), high wealth status (AOR 4.01, 95% CI:2.93-5.50 for overweight and AOR 6.97, 95% CI:4.08-11.9 for obesity), and the use of hormonal contraception (AOR 1.24, 95% CI:1.07-1.41 for overweight and AOR 1.35, 95% CI:1.10-1.64 for obesity). Additionally, having higher education increased the odds of being obese (AOR 1.44, 95% CI:1.07-1.96) while being Christian increased the odds for being overweight (AOR 1.13, 95% CI:1.00-1.28). Conclusions The prevalence of overweight and obesity among women in Zimbabwe was high. The key social factors associated were older age, being married, being wealthy and the use of hormonal contraception. Having a higher education and being Christian also increased the risk of being obese and overweight respectively. The design of multi-faceted overweight and obesity reduction programs for women that focus on increasing physical activity and strengthening of social support systems are necessary to combat this epidemic.